Nucleophilic addition to carbonyl groups from qualitative to quantitative computational studies. A historical perspective - Eisenstein, Odile (Comptes Rendus. Chimie)
Nucleophilic addition to carbonyl groups is one of the most important reactions in organic synthesis. In the case of a prochiral carbonyl group, the preference for the addition of a nucleophile to one face of the ${π }$ system leads to unequal amounts of the two possible diastereoisomers. The mechanism of this reaction for various nucleophiles (especially the early main group hydride and the Grignard reagents) and the various noncyclic and cyclic aldehydes or ketones has fascinated computational chemists for nearly 40 years. This article describes the research that has been done on this topic, the incentive for the present author being that she started her research with this topic and is returning to it in recent years.